Discussion on the article by Babashkin V.V., Tolstov S.I. «Collectivization as a page of history and its place in the national ideology of modern Russia» - V. V. Kondrashin; O. M. Verbitskaya; A. E. Busygin; I. V. Goncharova; P. P. Marchenya; V. N. Tomilin (Вестник Самарского университета: История, педагогика, филология)
This article presents the opinions of a number of leading Russian researchers, the subject of discussion of whom were the provisions expressed by Doctor of Historical Sciences, Professor V.V. Babashkin and Candidate of Historical Sciences, Associate Professor S.I. Tolstov. The authors of the article «Collectivization as a page of history and its place in the national ideology of modern Russia» published in the previous issue of the journal focused their attention on studying the formation of the «Soviet» version of collectivization of the peasant village. Based on the concept that the national ideology of the modern Russian Federation should be based on adequate ideas about the main events of the Soviet period, they come to the conclusion that it was peasant studies that should have become one of the most significant tools for historical and sociological research into the history of the country. The vivid and polemical presentation of the material and the undoubted demand in such a series of publications aroused the active interest of a number of well-known historians, primarily those involved in agrarian issues. Despite a number of serious critical comments during the exchange of opinions, the majority of researchers participating in the discussion recognized the significance and urgency of raising such issues and the need to develop a specific position for the development of modern historical science